Synthesis of New Dialkyl 2,2′-[Carbonylbis(azanediyl)]dibenzoates via Curtius Rearrangement - Yassine, Hasna; Bouali, Jamila; Oumessaoud, Asmaa; Ourhzif, El Mahdi; Hamri, Salha; Hafid, Abderrafia; Khouili, Mostafa; Pujol, Maria Dolors (Synthesis, 2021)
The 2-(alkylcarbonyl)benzoic acids obtained by esterification of phthalic anhydride are converted into azide derivatives: alkyl 2-[(azidocarbonyl)amino]benzoates and to ureas: dialkyl 2,2′-[carbonylbis(azanediyl)]dibenzoates. These transformations were carried out using classical Curtius rearrangement conditions in the presence of diphenylphosphoryl azide (DPPA) in a basic medium, followed by hydrolysis. Subsequently, a final condensation reaction of these urea derivatives enabled us to obtain, for the first time, the new alkyl derivatives, alkyl 2-[2,4-dioxo-1,2-dihydroquinazolin-3(4H)-yl]benzoates. All the new compounds obtained in satisfactory yields were characterized by 1H and 13C NMR, and by X-ray crystallographic analysis.
Keywords: phthalic anhydride; Curtius rearrangement; azide; acyl azide; urea